Neonatal Outcomes in Women with Pre-Eclampsia in a Tertiary Care Hospital - Mazhar Ali, Fazal Badshah, Saad Farid, Sumbal Afzal Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the frequency of adverse neonatal outcomes in women with pre-eclampsia. Methods: This case series containing 100 patients with diagnosis of pre-eclampsia was conducted in Saidu teaching hospital Swat from April-2022 to January-2023. The women were followed till delivery of baby. The primary study endpoint was neonatal outcomes, which were labelled in-terms of pre-mature birth, birth status, APGAR score at 5 minutes, NICU admission, and in-hospital death. Results: Mean age was 31.2±3.5 years, majority of patients; 44% were multiparous. Cesarean section was performed in 66% patients. Regarding neonatal outcomes, pre-term birth rate was 53%, still birth occurred in 12% patients. 46% neonates had normal birthweight, 35% were of low birthweight and 19% were of very low birthweight. NICU admission was needed in 58% neonates and 16% neonates died before discharge. Conclusion: There is a high frequency of adverse neonatal outcomes in women with pre-eclampsia. Optimizing obstetric and neonatal care can help to reduce these adverse outcomes. Keywords: pre-eclampsia, still birth, low birthweight, APGAR score, mortality.